An Interpretive Description of Sociocultural Influences on Diabetes Self-Management Support in Nigeria. (September 2022) - Iregbu, Sandra Chinwe; Duggleby, Wendy; Spiers, Jude; Salami, Bukola
The purpose of this study is to explore how Nigeria's social and cultural environment influences professional diabetes self-management support practices. This interpretive descriptive study is based on two diabetes clinics in southeastern Nigeria. Nineteen healthcare providers, including nurses, were purposely selected and engaged in participant observation and interviews. Concurrent data generation and analysis facilitated iterative constant comparative analysis. Findings show significant factors influencing diabetes self-management support include belief in the supernatural origin of diabetes, individual–family interdependence, myths and limited understanding of diabetes, lack of health insurance, poverty, and the rigidity of a hierarchical acute care model of diabetes services. Thus, there is an urgent need to adapt diabetes self-management support strategies to fit people's contexts. By doing so, specific challenges in the healthcare system can directly be addressed while capitalizing on identified strengths and adapting select strategies that constructively foster person-centered and culturally appropriate care.